Arabidopsis G-protein β subunit AGB1 represses abscisic acid signaling via attenuation of the MPK3-VIP1 phosphorylation cascade - Xu, Dongbei (Journal of experimental botany, 2024)
© The Author(s) 2023. Published by Oxford University Press on behalf of the Society for Experimental Biology. All rights reserved. For permissions, please email: journals.permissionsoup.com.